Separation of the impact of residual stress and microstructure on the fatigue performance of LPBF Ti-6Al-4V at elevated temperature. (July 2021) - Mishurova, Tatiana; Artzt, Katia; Rehmer, Birgit; Haubrich, Jan; Ávila, Luis; Schoenstein, Frédéric; Serrano-Munoz, Itziar; Requena, Guillermo; Bruno, Giovanni
Highlights: Fatigue tests at elevated temperature (300 °C) of LPBF Ti-6AL-4V. Contributions of defects, microstructure and residual stress to fatigue performance are separated. Tensile surface residual stress decreased fatigue performance for as-built condition. Effect of residual stress on fatigue performance is only discernible at the low strain amplitude. HIP is more effective than heat treatments in increasing the fatigue life. Abstract: Manufacturing defects, high residual stress (RS), and microstructures affect the structural integrity of laser powder bed fusion (LPBF) Ti-6Al-4V. In this study, the individual effect of these factors on fatigue performance at elevated temperature (300 °C) was evaluated. Material in as-built condition and subjected to post-processing, including two heat treatments and hot isostatic pressing, was investigated. It was found that in the absence of tensile RS, the fatigue life at elevated temperature is primary controlled by the defects; and densification has a much stronger effect than the considered heat treatments on the improvement of the mechanical performance.